2017
DOI: 10.1177/0284185117717762
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatment strategy for advanced hepatocellular carcinoma: combination of conventional transcatheter arterial chemoembolization and modified method with portal vein occlusion for cases with arterioportal shunt: a preliminary study

Abstract: Background A novel strategy to combine conventional transcatheter arterial chemoembolization (TACE) and TACE during portal vein occlusion (TACE-PVO) in the presence of high-flow arterioportal shunt (APS) has been developed to treat hepatocellular carcinoma (HCC) with portal invasion. Purpose To evaluate the efficacy of this strategy. Material and Methods Twenty-five cases of HCC with portal invasion, treated between April 2006 and December 2015, were evaluated. Balloon occlusion of the portal venous outlet was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have reported that APS is a poor prognostic factor in HCC patients because such patients are often associated with portal hypertension, refractory ascites, bleeding of esophageal and gastric varices, and hepatic encephalopathy 14. Due to the high risk of developing hepatic failure in patients with HCC and APS, cTACE is sometimes contraindicated 15. To the best of our knowledge, there is no standard treatment for the embolization of APS to date, and various embolic materials have been introduced, such as coils, gelatin sponges, absolute ethanol, glue, balloon-assisted embolization devices, and PVA particles 3,4,79,1619.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that APS is a poor prognostic factor in HCC patients because such patients are often associated with portal hypertension, refractory ascites, bleeding of esophageal and gastric varices, and hepatic encephalopathy 14. Due to the high risk of developing hepatic failure in patients with HCC and APS, cTACE is sometimes contraindicated 15. To the best of our knowledge, there is no standard treatment for the embolization of APS to date, and various embolic materials have been introduced, such as coils, gelatin sponges, absolute ethanol, glue, balloon-assisted embolization devices, and PVA particles 3,4,79,1619.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this research, a therapeutic strategy was given preference for better treatment of patients with stable intrahepatic tumours and severe SPH. Two cases of tumour thrombus–related portal hypertension were caused by arterioportal fistula due to tumour invasion, which is called “dynamic portal hypertension” [ 36 , 37 ]. The portal vein pressure in such cases is usually very high because of the connection between the hepatic artery branches and the portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…Although arterial supply of a liver segment is compromised after embolization, a patent portal axis compensates hepatocytes perfusion thus reducing damage to healthy liver. Transarterial embolization in the setting of portal thrombosis or invasion is relatively contraindicated although it can be performed if other therapies are unavailable [38].
Fig.
…”
Section: Transcatheter Therapymentioning
confidence: 99%